The perceptions of employees towards tipping and motivation in the hotel industry - Kazembe Clotildah; Mapingure Charity; Chimutingiza Felistas; Munyoro Tatenda (African Journal of Hospitality, Tourism and Leisure, 2014)

(untitled)
Restaurant tipping has been taken as a bone of contention which discriminates front and back employees involved with the service delivery in a hotel set- up. Monetary benefits affect worker motivation to some extent. Hence the study sought to analyze employee views on tipping and motivation. A lot of confusion and abhorrence has been created as to whom exactly should benefit from the tips servers get from guests. Qualitative research design was used to assess the extent to which tips are perceived as a reward for good service and how this influences worker motivation. Results showed that tipping is a two barreled tool where it can be a motivational tool to those who are tipped and a demotivator to those who are not tipped. The implication of the study is a service charge system to share tips is required to motivate all employees since the guest experience is a product of collective effort from almost all the employees in a hotel establishment.